Challenges to the Development of Intercultural Communication Competence: A Study from the Tertiary Students' Perspectives - Nguyen, Hong-Thu Thi (Journal of Social and Scientific Education, 2025)
This paper aims to study the challenges to the development of intercultural communication competence from the perceptions of students of the 44th course of English Language at Hanoi Law University, to point out the problems caused by the challenges, and propose some practical strategies to improve the effectiveness of intercultural communication. The study used a mixed-method approach, combining qualitative and quantitative methods. Questionnaires and interviews were the main instruments utilized to collect the quantitative and qualitative data.  The results show that the participants highly agree with the views on intercultural challenges such as cultural knowledge, language, ethnocentrism, uncertainty, stereotypes, prejudice, and discrimination. Challenges have caused many problems affecting the effectiveness of intercultural communication. Some solutions to improve intercultural communication competence have been noted, such as raising cultural awareness, changing attitudes positively in communication, improving cross-cultural communication skills, and actively participating in activities related to foreign cultures. This paper contributes valuable insights into the existing intercultural communication theory and offers further recommendations for fostering intercultural communication competence in higher educational environments.